Stent Assisted Coil Embolization: the Treatment of Wide-necked, Dissecting, and Fusiform Aneurysms - Irie, K. (Centauro S.r.l., 2003)
Stent assisted coil embolization is a useful therapeutic modality for wide-necked and geometrically difficult aneurysms, as the stent provide a buttress that allows for coil deposition while preventing coil haerniation into the parent vessel lumen, and placement of an endovascular stent within the parent artery across the aneurysm neck may divert the blood from the aneurysm inflow tract and promote intra-aneurysm stasis and thrombosis. We report herein a 3 patients treated with endovascular stent-assisted coil embolization for symptomatic or enlarging wide-necked, dissecting, and fusiform aneurysms of the carotid and vertebrobasilar arteries. One patient had intracranial mass effect, the second had subarachnoid haemorrhage, and the third had angiographic evidence of enlarging aneurysm. The aneurysm was located in the petrous segment of internal carotid artery in one patient and in the intracranial vertebral artery in the other two patients. For all patients, we used balloon expandable stent (such as GFX, S-670) in this technique. Complete obliteration of the aneurysms could be achieved in all cases, with preservation of distal circulation.